Considerações sobre o tratamento das mastites1 - Langoni, Helio [UNESP]; Salina, Anelise [UNESP]; Oliveira, Gabriela Capriogli [UNESP]; Junqueira, Nathália Brancato [UNESP]; Menozzi, Benedito Donizete [UNESP]; Joaquim, Sâmea Fernandes [UNESP] (My University, 2017)
Mastites are considered a major problem on animals for milk production. Changes the milk composition and increases the somatic cell count (SCC). The microorganism involved in the disease may be infectious origin such as Staphylococcus aureus or environmental such as Escherichia coli. Bacterial culture is a diagnostic tool and aids in the detection of pathogenic causing masitis. However factor such as phagocytosis may result a negative result. When established a mastitis control program early diagnose and the initiation of appropriate treatment of clinical cases are fundamental for achieving the goals and success is related to the pathogen involved. The indication of treatment of long duration, or extended therapy has improved the response to the treatment in cases of matitis by S. aureus, however with 30-50% of cure. From the view point of handling of animals, given the high infectiousness of this pathogen, its persistence in the herd and cost-effective as a function of response to treatment often has prioritized the animal's discard in order to control the mastitis cases in properties. Control measures are very important to contribute the reduction of cases of mastitis symptoms by this pathogen. The indication of intramammary treatment associated with systemic has power effective in cases of mastitis by E. coli, whose acute cases present with sepsis and toxemia. Also address aspects of alternative treatments of mastitis, mainly used in the organic process of milk production.
Considerations on the treatment of mastitis
Keywords: Bovine mastitis; Control program; Extended therapy